In Vivo Treatment With Granulocyte Colony-Stimulating Factor Does Not Delay Apoptosis in Human Neutrophils by Increasing the Expression of the Vacuolar Proton ATPase. (1st January 2002) - Zimbelman, Julie; Thurman, Gail; Leavey, Patrick J.; Ellison, Misoo C.; Ambruso, Daniel R.
Abstract : Background: Neutrophils die by apoptosis, and in vivo administration of granulocyte colony-stimulating factor (G-CSF) delays this apoptotic cell death. G-CSF administered in vitro correlates delayed apoptosis with upregulation of the vacuolar proton ATPase (v-ATPase). Because this enzyme requires assembly of membrane and cytosolic domains to function, we hypothesized that in vivo G-CSF would increase synthesis and assembly of v-ATPase components to delay apoptosis. Methods: Volunteers received G-CSF for 5 days, and each had a paired control. Neutrophils were isolated from subjects before the first and after the fifth injection. Proteins from cytosol or plasma membrane or from whole cell lysates were resolved by SDS-polyacrylamide gel electrophoresis and immunoblotted with antibody to the 33kDa v-ATPase E subunit. Densitometry quantified immunoreactivity. Results: No significant increase on the E subunit occurred between treated and control groups. Conclusion: In vivo G-CSF does not increase the amount of v-ATPase in neutrophils. Although G-CSF in vivo delays apoptosis, the mechanism(s) by which this occurs is not known.